Integration of Entrepreneurship Development in the Almajiri Educational System in Katsina State Nigeria: Array - Mamman, Aliyu; Gbolagade, Oladejo Lukman; Garba, Abdulkarim; Kayode, Olaoye Ismail; Abubakar, Ahmadu; Lekan, Olusegun Kazeem; Braide, Sonny Emmanuel; Shagari, Jibrin Nuhu; Morenikeji, Abdulrahaman Abdulrazak; Ogbu, Orinya John (Acta Universitatis Danubius. Œconomica, 2020)
Despite the establishment of Almajiri formal education in 2012, Nigeria is still experiencing high number of almajiri across the country most especially, the Northern parts. The failure of the recent almajiri formal schools in Northern Nigeria to reduce or eradicate the number of almajiri children roaming the streets and begging for alms calls for a great concern. Therefore, this study aimed at integrating almajiri system of education with the basic entrepreneurship skills programmes and to assess the effect of the integration on the entrepreneurship development, using 144 valid responses received from mallams from Almajiri schools, staff of ministries of education and boards of Arabic and Islamic studies across the 3 senatorial districts of Katsina State. The study utilized convenience and purposive sampling techniques in the selection of the respondents due to heterogeneous nature of the population and the absence of knowledge about the sample frame. Descriptive statistics such as frequencies, percentages, mean, minimum and maximum values were used in data presentation; while multiple regression technique was used in assessing the effect of the study variables. Major findings indicate that integration of Almajiri system of education with basic entrepreneurship skills has positive and significant effect on entrepreneurship development. The study therefore concludes that integration of Almajiri system of education with basic entrepreneurship skills is achievable and that it will enhance entrepreneurship, and ultimately economic, activities in the state. The study recommends that the Almajiri system of education should be integrated with entrepreneurship skills; as doing so will foster entrepreneurship development.